2020
DOI: 10.4269/ajtmh.20-0491
|View full text |Cite
|
Sign up to set email alerts
|

Liver Function Test Abnormalities in Experimental and Clinical Plasmodium vivax Infection

Abstract: Liver transaminase elevations after treatment in malaria volunteer infection studies (VISs) have raised safety concerns. We investigated transaminase elevations from two human Plasmodium vivax VISs where subjects were treated with chloroquine (n = 24) or artefenomel (n = 8) and compared them with studies in Thailand (n = 41) and Malaysia (n = 76). In the VISs, alanine transaminase (ALT) increased to ³ 2.5 × upper limit of normal (ULN) in 11/32 (34%) volunteers, peaking 5-8 days posttreatment. Transaminase elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 49 publications
3
16
1
Order By: Relevance
“…The adverse events reported for both studies are in keeping with previous IBSM studies [9][10][11]28,29]. The asymptomatic raised liver enzymes, with no associated signi cant rise in bilirubin, have been reported in previous IBSM studies [30,31], sporozoite VIS [32] and in naturally occurring malaria [30,33]. Similarly, the reduction in white cell counts, especially lymphopenia and neutropenia have previously been reported in IBSM VIS, sporozoite VIS and clinical malaria [12,16,[34][35][36].…”
Section: Discussionsupporting
confidence: 85%
“…The adverse events reported for both studies are in keeping with previous IBSM studies [9][10][11]28,29]. The asymptomatic raised liver enzymes, with no associated signi cant rise in bilirubin, have been reported in previous IBSM studies [30,31], sporozoite VIS [32] and in naturally occurring malaria [30,33]. Similarly, the reduction in white cell counts, especially lymphopenia and neutropenia have previously been reported in IBSM VIS, sporozoite VIS and clinical malaria [12,16,[34][35][36].…”
Section: Discussionsupporting
confidence: 85%
“…Plasmodium is a genus of single-cell protozoa that causes malaria, which may enter hepatocytes for dormancy or reproduction and lead to cell rupture, release merozoites and invade red blood cells (17). Although Plasmodium stays in the liver and causes black colouring of the tissue due to the deposition of the Plasmodium pigment, it does not damage liver function (18). Our previous studies have demonstrated that Plasmodium infection inhibits tumour development and metastasis in a murine Lewis lung cancer model (19)(20)(21)(22)(23)(24).…”
Section: Plasmodium Infection Prevents Recurrence and Metastasis Of Hmentioning
confidence: 99%
“…Of note, there were no significant deviations in albumin or bilirubin in our volunteer cohort (Minassian et al, in preparation) indicating that the biosynthetic and metabolic functions of the liver have not been compromised. Elevations in ALT are therefore a marker of asymptomatic collateral tissue damage in CHMI, as previously suggested (33). Another limitation of this study is that infections had to be terminated at a parasite density much lower than would be observed in endemic settings.…”
Section: Discussionmentioning
confidence: 73%
“…Drug treatment is also unlikely to explain the increase in ALT observed in most volunteers. Liver injury is a common feature of clinical and experimental malaria and occurs independently of the drug used or the treatment regime (32)(33)(34). Furthermore, abnormal ALT levels significantly decrease 7-days after drug treatment in patients with severe malaria (80), suggesting that infection or inflammation is the driver of hepatocellular death.…”
Section: Discussionmentioning
confidence: 99%